Protest policing in Hong Kong: maintaining professionals and solidarity in the face of renewed political challenges - Lin, Tingjin; Burns, John P. (2016)
Protest has been a feature of Hong Kong political life since the mid-1950s. The structure of protest policing in Hong Kong should be seen from institutional, organizational, and individual levels. We examine the norms and values, staffing, professionalism, and individual motivation of police officers. Based on a questionnaire and performance data, we seek to understand police behavior in the context of increasing protest in Hong Kong. - Reproduced.
Keywords: Protest movements - Hong Kong; Police - Hong Kong; Police